(untitled) (Journal of Comparative & International Higher Education, 2023)
During a global pandemic, many students in 2020-2021 turned to peer-facilitated academic support through supplemental instruction (SI) to succeed. In this study, proficient students were hired as SI Leaders and trained to facilitate study sessions in a collaborative virtual learning environment. The impact of online SI support is assessed upon subgroups of 4,831 students enrolled in difficult courses at a four-year public university. Mean course GPAs and pass rates of international students, students of color, and white students with varying levels of SI session attendance were examined. One-way ANOVA and chi-square test results reveal significant differences by level of attendance for students of color and white students, with higher mean course GPAs and pass rates associated with higher levels of attendance at SI sessions for all three subgroups. These results are consistent with feedback from SI attendees and convey the significance of programs like SI, especially in times of crisis.